Life in extreme environments: single molecule force spectroscopy as a tool to explore proteins from extremophilic organisms. (1st April 2015) - Tych, Katarzyna M.; Hoffmann, Toni; Batchelor, Matthew; Hughes, Megan L.; Kendrick, Katherine E.; Walsh, Danielle L.; Wilson, Michael; Brockwell, David J.; Dougan, Lorna
Abstract : Extremophiles are organisms which survive and thrive in extreme environments. The proteins from extremophilic single-celled organisms have received considerable attention as they are structurally stable and functionally active under extreme physical and chemical conditions. In this short article, we provide an introduction to extremophiles, the structural adaptations of proteins from extremophilic organisms and the exploitation of these proteins in industrial applications. We provide a review of recent developments which have utilized single molecule force spectroscopy to mechanically manipulate proteins from extremophilic organisms and the information which has been gained about their stability, flexibility and underlying energy landscapes.